Pelaksanaan Pendaftaran Tanah Sistematis Lengkap Di Kabupaten Bengkulu Tengah Perspektif Hukum Islam - Putri, Deriska Wulanda (UIN Fatmawati Sukarno Bengkulu, 2021)
Abstract : In Islamic law, the relationship between Complete Systematic Land Registration and Maqasyid Al-Sharia is through land registration, the rights of citizens to protect their objects in the form of land can be realized and that is also the goal of Maqasyid Al-Shariah to be achieved. It is described in this paper, how is the implementation of PTSL, how is the legal certainty of ownership of land rights in PTSL, and how is the Islamic legal perspective on the implementation of PTSL and ownership of land rights. In order to speed up the land registration process in Indonesia, a new breakthrough was issued, namely the Complete Systematic Land Registration or abbreviated as PTSL which is regulated through the provisions of the Minister of Agrarian Regulation Number 6 of 2018 concerning Complete Systematic Land Registration. Regarding legal certainty, things that need to be considered in land registration are the principle of publicity, installation of boundary signs and the application of the principle of Contradicture Delimitation or the presence of the owner and witnesses bordering. The relationship between Islamic law and land registration is a form of government responsibility in carrying out the mandate of the Basic Agrarian Law. This research is a qualitative-empirical research by means of field research or observation and conducted by interview. Keywords: Complete Systematic Land Registration, Maqasyid Al-syari’ah Abstrak : Di dalam hukum Islam hubungan antara pendaftaran Tanah Sistematis Lengkap dan maqasyid Alsyariah adalah melalui pendaftaran tanah, hak-hak warga negara untuk melindungi bendanya berupa tanah dapat terwujud dan itu juga merupakan tujuan dari maqasyid Al-Syariah yang hendak dicapai. Dijelaskan di dalam tulisan ini, bagaimana pelaksanaan PTSL, bagaimana kepastian hukum kepemilikan hak atas tanah dalam PTSL, dan bagaimana Perspektif hukum islam terhadap Pelaksanaan PTSL dan kepemilikan hak atas tanah. Guna mempercepat proses pendaftaran tanah di Indonesia, dikeluarkanlah terobosan baru yaitu Pendaftaran Tanah Sitematis Lengkap atau yang disingkat PTSLyang diatur melalui ketentuan Peraturan Menteri Agraria Nomor 6 Tahun 2018 tentang Pendaftaran Tanah Sistematis Lengkap. Terkait kepastian hukum, hal-hal yang perlu diperhatikan dalam pendaftaran tanah yaitu, asas publisitas, pemasangan tanda batas dan penerapan asas Contradicture Delimitasi atau kehadiran pemilik dan saksi berbatasan. Hubungan hukum islam dan pendaftaran tanah merupakan sebuah bentuk tanggungjawab pemerintah dalam menjalankan amanat Undang-undang Pokok Agraria. Penelitian ini merupakan penelitian kualitatif-empiris dengan cara field research atau observasi dan dilakukan dengan wawancara. Kata kunci :Pendaftaran Tanah Sistematis Lengkap, Maqasyid Al-syari’ah